The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.ijmm.2014.01.002
|View full text |Cite|
|
Sign up to set email alerts
|

Escherichia coli isolates from inflammatory bowel diseases patients survive in macrophages and activate NLRP3 inflammasome

Abstract: Crohn’s disease (CD) is a multifactorial pathology associated with the presence of adherent-invasive Escherichia coli (AIEC) and NLRP3 polymorphic variants. The presence of intracellular E. coli in other intestinal pathologies (OIP) and the role of NLRP3-inflammasome in the immune response activated by these bacteria have not been investigated. In this study, we sought to characterize intracellular strains isolated from patients with CD, ulcerative colitis (UC) and OIP, and analyze NLRP3-inflammasome role in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
75
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 54 publications
7
75
0
2
Order By: Relevance
“…Our results further support the idea that AIEC might have more than one mechanism to interact with M cells and access the underlying macrophages present in the lymphoid tissue. The survival within murine macrophages by AIEC isolates has been well described (3), where the survival at 24 h postinfection can range from 32 to 100% of bacteria phagocytosed in the case of the Crohn's disease-associated strains (4,51). In our study, the survival of NRG857c in human macrophages at 24 h postinfection was 32.42%, which is consistent with what has been reported for other AIEC strains.…”
Section: Discussionsupporting
confidence: 90%
“…Our results further support the idea that AIEC might have more than one mechanism to interact with M cells and access the underlying macrophages present in the lymphoid tissue. The survival within murine macrophages by AIEC isolates has been well described (3), where the survival at 24 h postinfection can range from 32 to 100% of bacteria phagocytosed in the case of the Crohn's disease-associated strains (4,51). In our study, the survival of NRG857c in human macrophages at 24 h postinfection was 32.42%, which is consistent with what has been reported for other AIEC strains.…”
Section: Discussionsupporting
confidence: 90%
“…The qPCR results suggested that this increase was due to E. coli, and this group is of particular interest, as previous studies have reported an increased virulent potential of E. coli, such as adhesive capacity, invasive capacity, toxin production, and inflammatory cytokine stimulation, in human patients with IBD. 29,30 Adherent and invasive E. coli strains have been reported specifically in Boxer dogs with granulomatous colitis. 31 Whether the virulent potential of E. coli plays a similar role in other forms of canine inflammatory bowel disease remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…AIEC survival and replication in macrophages is promoted by the stress protein HtrA,67 the thiol-disulfide oxidoreductase DsbA,68 the RNA-binding protein Hfq69 and the FAD-dependent oxydoreductase IbeA70 that play a role in surviving reactive oxygen species (ROS) (table 1). In response to AIEC infection, tumour necrosis factor α (TNF-α)35 71 72 and other proinflammatory cytokines73 are released, further enhancing dysbiosis and proliferation of AIEC without inducing host cell death. AIEC are able to exploit host mechanisms of apoptosis by increasing S-nitrosylation and proteasomal degradation of caspase-3 in infected macrophages,74favouring their own intracellular replication through modulation of the ubiquitin proteasome system in infected-IEC,75 76 and through the release of exosomes from infected cells 77.…”
Section: Definition Of Aiecmentioning
confidence: 99%